Omega-3 docosahexaenoic acid induces pyroptosis cell death in triple-negative breast cancer cells - Pizato, Nathalia Marcolini Pelucio (2018)
The implication of inflammation in pathophysiology of several type of cancers has been under intense investigation. Omega-3 fatty acids can modulate inflammation and present anticancer effects, promoting cancer cell death. Pyroptosis is an inflammation related cell death and so far, the function of docosahexaenoic acid (DHA) in pyroptosis cell death has not been described. This study investigated the role of DHA in triggering pyroptosis activation in breast cancer cells. MDA-MB-231 breast cancer cells were supplemented with DHA and inflammation cell death was analyzed. DHA-treated breast cancer cells triggered increased caspase-1and gasdermin D activation, enhanced IL-1β secretion, translocated HMGB1 towards the cytoplasm, and membrane pore formation when compared to untreated cells, suggesting DHA induces pyroptosis programmed cell death in breast cancer cells. Moreover, caspase-1 inhibitor (YVAD) could protect breast cancer cells from DHA-induced pyroptotic cell death. In addition, membrane pore formation showed to be a lysosomal damage and ROS formation-depended event in breast cancer cells. DHA triggered pyroptosis cell death in MDA-MB-231by activating several pyroptosis markers in these cells. This is the first study that shows the effect of DHA triggering pyroptosis programmed cell death in breast cancer cells and it could improve the understanding of the omega-3 supplementation during breast cancer treatment.